External debt and growth: role of stable macroeconomic policies - Dey, Sima Rani (2020)
Purpose: This study aims to examine the impact of external debt on economic growth in Bangladesh within a broader macroeconomic scenario. Design/methodology/approach: In the process of doing so, it assesses the empirical cointegration, long-run and short-run dynamics of the concerned variables for the period of 1980–2017 applying the autoregressive distributed lag (ARDL) bounds testing approach to cointegration. First, debt-gross domestic product linkage explores the impact of external debt impact on economic growth using a set of macro and country risk variables, and then this linkage is also analyzed along with a newly formed macroeconomic policy (MEP) variable using principal component analysis. Findings: The study results reveal the negative impact of external debt on GDP growth, but the larger positive impact of MEP index indicates that this adverse effect of debt can be mitigated or even nullified by sound MEP and appropriate human resource policy. Originality/value: The dynamic effects of different shocks (external debt and macro policy variable) on economic growth by vector autoregression impulse response function also confirm our ARDL findings. DOI: https://doi.org/10.1108/JEFAS-05-2019-0069